Distribution of Mandibular Fractures Based on Age, Gender, Etiology, and Fracture Region at Abdoel Wahab Sjahranie Hospital Samarinda from 2019 to 2023 - Gayatri, Amanda Putri; Pramasari, Cristiani Nadya; Cahya, Wahyuni Dwi; Anitasari, Silvia; Irawiraman, Hadi (Jurnal Sains dan Kesehatan, 2025)
Mandibular fracture is one of the fractures in the facial area and is most often caused by trauma. A hard impact to the face can result in a fracture of the mandible. This research aims to investigate the distribution of mandibular fracture based on age, gender, etiology, and fracture region at Abdoel Wahab Sjahranie Hospital Samarinda from 2019 to 2023. This research is quantitative research using descriptive observational research design. The results of this research showed that adolescent age from 12 to 25 years old was the age group in which mandibular fracture cases were found the most, with 34 cases (54%) in this research were from that age group. In terms of gender, mandibular fracture cases were found more in male samples, with 52 cases (82.5%) were male. Traffic accident was the most common etiology of mandibular fractures found, comprising of 47 cases (74.6%) from the total number of cases in this research. The most common fracture region found in this research was the parasymphysis region, with 13 cases (20.6%) in this research had parasymphyseal fracture.   Keywords:          Distribution, Mandibular Fracture, Mandibular Fracture Region